2009
DOI: 10.1007/s10238-009-0061-1
|View full text |Cite
|
Sign up to set email alerts
|

In vivo modulation of the expressions of Fas and CD25 by intravenous immunoglobulin in common variable immunodeficiency

Abstract: Although the presence of physiologic anti-CD95 (Fas, APO-1) autoantibodies in intravenous immunoglobulin (IVIG) preparations is known, the effects of these antibodies in patients with common variable immunodeficiency are unclear (CVID). The aim of the study was to assess the effects of IVIG in Fas expression, activation markers and the subsets of T cells in patients with CVID. We studied 15 cases with CVID and 10 healthy controls with no signs of immunodeficiency. The Fas expression of T cells, activation mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Thus, IVIg increases the TNFa and IL-2 in vivo in CVID patients with unchanged IFN-g expression [59]. It was also suggested that IVIg by up-regulating the Fas expression on CD4þT cells, controls autoimmunity in CVID patients [60]. Further, we have previously demonstrated that IVIg rescues defective differentiation of DC from both CVID and X-linked agammaglobulinemia patients with an enhanced production by DC of anti-inflammatory cytokine IL-10 [61,62].…”
Section: Discussionmentioning
confidence: 91%
“…Thus, IVIg increases the TNFa and IL-2 in vivo in CVID patients with unchanged IFN-g expression [59]. It was also suggested that IVIg by up-regulating the Fas expression on CD4þT cells, controls autoimmunity in CVID patients [60]. Further, we have previously demonstrated that IVIg rescues defective differentiation of DC from both CVID and X-linked agammaglobulinemia patients with an enhanced production by DC of anti-inflammatory cytokine IL-10 [61,62].…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, a significant decrease in CD4 + /CD8 + ratio is observed in PD patients as well [69-71], possibly accounted for by an increased susceptibility to apoptosis observed in CD4 + T cells, consequent of Fas overexpression [72]. IVIg has been reported to modulate the level of expression of Fas and FasL and to inhibit FasL-dependent apoptosis, in both in vivo and in vitro studies [34,73-75]. This action of IVIg on the Fas/FasL pathway could have been translated into neurorestoration.…”
Section: Discussionmentioning
confidence: 99%
“…IVIG reduces expression of the activation markers Ki67, CD38, and HLA-DR on CD8 + T cells [94]. However, Artac et al [96] reported that expression of CD69 and HLA-DR by CD8 + T cells is not affected by IVIG. The immunological mechanisms by which IVIG can normalize T-cell counts and function in CVID patients remains unclear, but Dolcino et al [97] reported that lower expression of LEPR, a major gene in CD4 + T-cell proliferation, returned to normal values after IVIG treatment [97].…”
Section: Effects Of Ivig On T Cells In Cvid Patientsmentioning
confidence: 99%